Complexity and individual plan of nursing care of patients with intraaortic balloon contrapulsation - Krymska, Bożena (Nursing Problems / Problemy Pielęgniarstwa, 2007)
Intraaortic balloon contrapulsation (IABP) is the most common method of mechanical support for heart failure. It is used in both contemporary cardiology and cardiosurgery. The aim of that paper is to show the individual and complex approach in taking care of patients treated with IABP. This study is based on individual, medical documentation of 48 cardiologic patients who required IABP for heart failure, the results allowed to create the individual plan of nursing care with regarding the patients asbiopsychosocial intities.